Augmented Reality-Based Learning Media Training to Develop Elementary School Teachers' Creativity - Sahronih, Siti; Sholeha, Herisa Hardiyanti; Reza, Mohamad Fahmi; Wicaksono, Jatu Wahyu; Nurfadillah, Intan; Savitri, Sofie (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
Learning using technology is currently the main thing because it has entered the Society 5.0 era. This community service activity aims to provide opportunities for elementary school teachers in Cirebon City to conduct training on the use of augmented reality-based teaching media to support the development of their creativity and role in the learning process in the classroom. This activity has a target, namely teachers who are members of the Teacher Working Group Forum (FKKG) who are members of the board of directors of a total of 40 teachers from representatives of their respective schools in Cirebon City. This activity aims to: (1) develop the role of teachers in the digital economy era to better master technology in the learning process; (2) providing opportunities for elementary school teachers in Cirebon City to develop creativity in making interesting teaching materials; (3) facilitating teachers in creating digital augmented reality-based teaching materials; (4) utilizing AR technology to present interactive teaching media; and (5) support Merdeka Belajar-Kampus Merdeka (MBKM) program. This service activity uses the Participatory Action Research (PAR) method which includes activities that will be carried out ranging from identifying problems (to know), understanding (to understand), acting (to act), making changes (to change). The stages in this activity include (a) socialization and FGD; (b) the training process in several meetings; (c) the application of technology; (d) assistance and evaluation; (e) program sustainability, which provides broad opportunities for teachers to implement AR technology in learning and share knowledge with peers. The results of the training activities had a good response from the participants, including being able to increase the creativity of teachers in compiling AR learning media. In addition, the results of the questionnaire response have a score of 4.45 in the "excellent" category.